Effect of Product Quality and Brand Image Toward Purchasing Decisions Cap Lang Aromatherapy Eucalyptus Oil (A Case Study in PT. Surya Donasin Bogor) - Kuraesin, Ecin; Nasution, Abdul Haris; Muniroh, Leny (inovator, 2023)
The This writer aims to determine the effect of product quality and brand image on purchasing decisions of Cap Lang Eucalyptus Aromatherapy Oil at PT. Surya Donasin Bogor simultaneously and partially on purchasing decisions at PT. Surya Donasin Bogor. The number of samples used in this study amounted to 61 people consisting of customers at PT. Surya Donasin Bogor who filled out the questionnaires that were distributed. Data collection techniques by means of field research as for observation and questionnaires. Data analysis techniques used instrument tests consisting of validity tests, reliability tests, classic assumption tests consisting of normality tests, multicollinearity tests and heteroscedasticity tests, multiple linear regression analysis, hypothetical tests, namely partial tests and simultaneous tests. The purpose of this study was to determine whether product quality and brand image have an effect on purchasing decisions. The research results obtained (1) multiple linear regression equation Y = 3.387 + 0.289 + 0.426 and (2) simultaneous hypothesis f test with fcount of 67.378 with a ftable value of 3.156 meaning there is a significant influence between product quality (X1) and brand image (X2) there is a purchase decision (Y). (3) There is a partial effect of product quality with product quality getting a value of t: 2.503 and brand image partially with a value of t: 2.731. Thus it can be concluded that product quality and brand image influ-ence the purchasing decision of Cap Lang Eucalyptus Aromatherapy Oil at PT. Surya Donasin Bogor.